Deconversion from the Church of Jesus Christ of Latter-day Saints and the Quest for Identity - Wenger Jindra, Ines (Pastoral psychology, 2022)
Deconversion from the Church of Christ of Latter-day Saints (LDS) is often an arduous process and can lead to a sense of losing one’s identity. This article describes the stories of people who deconvert from the LDS church while making sense of the link between deconversion and identity. The manuscript is based on 18 interviews with people leaving the LDS church. While some of the deconverts had achieved a stable sense of identity at the time of the interview, others were still struggling with this task. This article attempts to understand these differences while also paying attention to the role of gender. The study also has implications for pastoral care and social work practice.